In vivo, contactless, cellular resolution imaging of the human cornea with Powell lens based line field OCT - Chen, Keyu; Abbasi, Nima; Wong, Alexander; Bizheva, Kostadinka (Scientific reports, 2024)
Potentially blinding corneal diseases alter the morphology of the human cornea. At the early stages of disease development, these changes occur at the cellular level. The ability to visualize and quantify such changes can lead to early diagnostics of corneal pathologies, which is pivotal for the long-term preservation of vision. Here we present a Powell Lens-based Line-Field Optical Coherence Tomography system that combines high spatial resolution (2.4 μm × 2.2 μm × 1.7 μm (x × y × z)) in biological tissue, sufficient to resolve individual cells, high sensitivity (90.5 dB), sufficient to image the semi-transparent human cornea, and fast image acquisition rate (~ 2,400 fps), sufficient to suppress most involuntary eye motion artifacts and allow for contactless, in-vivo imaging of the cellular structure of the human cornea. Volumetric images acquired in-vivo from corneas of healthy subjects show epithelial, endothelial and keratocytes cells, as well as sub-basal and stromal nerves. The system’s high axial resolution also allows for volumetric morphometry of the corneal endothelium, Descemet’s membrane and the pre-Descemet’s (Dua) layer.